Optimizing The Role Of Social Media As A Means Promotion Of Digital Marketing Of Tourism Ngenang Island Batam - Maldin, Siska Amelia; Sianipar, Baktivillo; Kartika Cahayani; Benget Rosalina; Adrian Nathanael Setijono (JURNAL KEKER WISATA, 2025)
This Community Service activity inspires the people of Ngenang that Ngenang Island has its own appeal to be marketed through the use of social media to promote tourism activities and enhance the economy of its residents. In particular, this activity allows lecturers and students to collaborate in finding the best solutions to the problems faced by the community. This activity involves lecturers and students in carrying out their threefold duties.